Respuesta :

Answer:

X = -2 and 4

Step-by-step explanation:

Move all of the terms to one side and set the equation to 0:

2x^2-14x+40-3x^2+16x-32 = 0

Then combine all like terms which would look like the following:

-x^2 + 2x + 8=0

Change the signs on both sides of the equation:

x^2 - 2x - 8 =0

Write -2x as a difference:

x^2 + 2x - 4x -8 = 0

Factor the expression:

x(x+2) x 4(x+2)=0

Factor out x+2 from the equation:

(x+2) (x-4)=0

Split into classes and then find the answer from there:

x+2=0

x-4=0

Work and explanation is attached
ACCESS MORE